Pidana Mati Bersyarat: Pergeseran Filosofi Pemidanaan Dari Retributif Ke Rehabilitatif Dalam KUHP Nasional - Aditia, Fanita; Setiawan, Beni; Kusuma Sumantri, Aditya; Ambron Ritonga, Wildan (PAMPAS: Journal of Criminal Law, 2026)
Law Number 1 of 2023 concerning the Criminal Code introduced the concept of conditional death penalty as a radical innovation in the Indonesian penal system. This study aims to analyze the normative construction of conditional death penalty as a manifestation of the shift in the paradigm of punishment from a retributive to a rehabilitative orientation. The research method used is normative legal research with a legislative, conceptual, and philosophical approach. Primary legal materials include the National Criminal Code and related laws and regulations, while secondary legal materials include doctrine, punishment theory, and relevant scientific literature. This study reveals that conditional death penalty is the result of a dialectical synthesis between the retributive and rehabilitative paradigms that produces a fundamental philosophical paradox. The main findings of the study indicate: First, the construction of conditional death penalty creates an ambiguous ontological status for convicts—"living in the shadow of death" during a ten-year probationary period, which is contrary to the principle of human dignity. Second, there is an epistemological contradiction in the parameters of "commendable attitudes and actions" as the basis for criminal conversion, considering that moral transformation is not something that can be verified objectively and scientifically. Third, efforts to transform the "death row phenomenon" from a torturous waiting period into a hopeful probationary period actually creates prolonged uncertainty that violates the principle of legal certainty. Fourth, this retributive-rehabilitative synthesis fails to achieve systemic coherence because it is impossible to rehabilitate someone back into society while the threat of execution remains. This study concludes that the conditional death penalty, rather than being a progressive solution, actually creates juridical-philosophical complexity that questions the ability of the national criminal justice system to realize dignified justice and true legal certainty. ABSTRAK Undang-Undang Nomor 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana mengintroduksi konsep pidana mati bersyarat sebagai inovasi radikal dalam sistem pemidanaan Indonesia. Penelitian ini bertujuan menganalisis konstruksi normatif pidana mati bersyarat sebagai manifestasi pergeseran paradigma pemidanaan dari orientasi retributif menuju rehabilitatif. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan perundang-undangan, konseptual, dan filosofis. Bahan hukum primer meliputi KUHP Nasional dan peraturan perundang-undangan terkait, sedangkan bahan hukum sekunder mencakup doktrin, teori pemidanaan, dan literatur ilmiah relevan. penelitian ini mengungkap bahwa pidana mati bersyarat merupakan hasil sintesis dialektis antara paradigma retributif dan rehabilitatif yang menghasilkan paradoks filosofis fundamental. Temuan utama penelitian menunjukkan: Pertama, konstruksi pidana mati bersyarat menciptakan status ontologis terpidana yang ambigu—"hidup dalam bayang-bayang kematian" selama masa percobaan sepuluh tahun, yang bertentangan dengan prinsip martabat manusia. Kedua, terdapat kontradiksi epistemologis dalam parameter "sikap dan perbuatan terpuji" sebagai basis konversi pidana, mengingat transformasi moral bukanlah sesuatu yang dapat diverifikasi secara objektif-ilmiah. Ketiga, upaya mentransformasi "death row phenomenon" dari masa tunggu yang menyiksa menjadi masa percobaan penuh harapan justru menciptakan ketidakpastian berkepanjangan yang melanggar asas kepastian hukum. Keempat, sintesis retributif-rehabilitatif ini gagal mencapai koherensi sistemik karena mustahil merehabilitasi seseorang untuk kembali ke masyarakat sementara ancaman eksekusi tetap menggantung. Penelitian ini menyimpulkan bahwa pidana mati bersyarat, alih-alih menjadi solusi progresif, justru menghasilkan kompleksitas yuridis-filosofis yang mempertanyakan kemampuan sistem pemidanaan nasional dalam mewujudkan keadilan bermartabat dan kepastian hukum yang hakiki.